Analysis of Arabic Learning Barriers Faced by Madrasah Aliyah Students and Teachers’ Efforts in Providing Pedagogical Solutions - M. Fachri Ihsan Nurbaehaqi; Ediat Ediat; R. Nasita Namia; Muhammad Asshiddieqy Puralam (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to identify the types of barriers to learning Arabic experienced by Madrasah Aliyah students in linguistic, psychological, and learning-environment aspects; to examine the internal and external factors contributing to these barriers; to analyze the pedagogical strategies and approaches implemented by teachers to overcome the challenges; and to evaluate the effectiveness of these pedagogical solutions in improving students’ Arabic language skills and learning motivation. The research employs a descriptive qualitative approach to portray the Arabic learning barriers at Madrasah Aliyah and to analyze teachers’ pedagogical solutions in a natural and contextual manner. Data are obtained through interviews, observations, and documentation, supported by both primary and secondary sources. The analysis applies the Miles and Huberman model through interactive processes of data reduction, presentation, and conclusion drawing to ensure accurate, objective, and comprehensive findings. The results show that barriers to learning Arabic among Madrasah Aliyah students are multidimensional, covering linguistic, psychological, and environmental aspects, and are influenced by both internal and external factors. Difficulties in phonology, vocabulary, and grammar are exacerbated by anxiety, low motivation, and limited language exposure. The learning environment and teaching methods also tend to be less supportive. Teachers apply linguistic, affective, communicative, and managerial strategies to reduce these barriers and gradually enhance students’ language acquisition.